Sintonia do controlador de umidade de um desumidificador de uma sala de arquivos - Nicolotte, João Henrique (2017)
This paper presents the tuning of a dehumidifier moisture controller for file room. Here is described the definition and types of dehumidification. It also presents the conditions for air treatment inside the room, preparation of the environment, equipment and data collection. The study presents a way to obtain the transfer function and the parameters to tuning the system. It also addresses the comparison between the controller found by software and the physical plant controller. The goal is to implement a precise moisture control system. Finally, we present the conclusions, such as the suggestion of future paper and the final results of the controller’s adjustment study with the influences of its parameters on the system.